Expression of the HPV18/E6 oncoprotein induces DNA damage - Cortés Gutiérrez, Elva Irene; García Vielma, Catalina; Aguilar Lemarroy, Adriana; Vallejo Ruíz, Veronica; Piña Sánchez, Patricia; Zapata Benavides, Pablo; Gosálvez, Jaime (2017)
This study investigated possible variations in DNA damage in HeLa cells with silenced expression of the HPV/E6 oncogene compared with HeLa cells with normal expression of the E6 oncogene using the DNA breakage detection-fluorescence in situ hybridization (DBD-FISH) technique and a whole human genome DNA probe. The variable levels of DNA breaks present were measured quantitatively using image analysis after whole-genome DNA hybridization. HeLa cells with silenced expression of the HPV18/E6 oncogene showed a significant decrease in DNA damage compared with parental cells with normal expression of the E6 oncogene. These results were confirmed by alkaline comet assay. In conclusion, we demonstrated a decrease in DNA damage in HeLa clones associated with low expression of the HPV/E6 oncogene. The significance of this decrease regarding the HPV life cycle and carcinogenesis requires further exploration.